Scented Root Extract (Vetiveria zizanioides L.) Inhibits Bacillus cereus Growth In-Vitro - Hapsari, Bramantyas Kusuma; Sahabuddin, Rosdiana; Vebrianty, Rizky Indah (Berkala Kedokteran, 2024)
Bacillus cereus, a gram-positive bacterium with a high incidence of causing infection through food, is a common cause of infection. Plant extract from Vetiveria zizanioides (L.) contains alkaloids, flavonoids, saponins, and tannins, and has been demonstrated to exhibit antibacterial action against other bacteria such as Staphylococcus aureus, Vibrio cholerae, Escherichia coli, Salmonella typhi, and Klebsiella pneumoniae. The purpose of this study is determining the antibacterial activity of vetiver root extract (Vetiveria zizanioides (L.)) against the growth of Bacillus cereus bacteria in vitro. In this experimental study, the inhibition effect of vetiver root extract against Bacillus cereus growth was measured using disc diffusion method. Extract consentraion used in this tudy were 60%, 80% and 100%. The diameter of area with no bacterial growth around disc (inbition zone) was measured and the average of diamter from four independent measurement was used to decide the sensitivity of bacteria towards the extract. The average measurement results from 60 percent concentration of extract were 6.70 mm, 7.04 mm for 80 percent concentration, and 7.05 mm for 100 percent extract concentration. The positive control, Amoxicillin 500 mg, had a diameter of 14.35 mm, whereas the negative control, sterile distilled water, had no impact. Bacillus cereus bacteria growth can be inhibited by Vetiveria zizanioides (L.) extract.